2019
DOI: 10.46701/apjbg.2019022019129
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle interactions with blood proteins and what it means: a tutorial review

Abstract: Nanoparticles find many uses in medicine and biomedical technology. Such applications imply that they must be colloidally stable and do not interact with proteins in the blood or blood serum. A nanoparticle put into the blood will instantaneously be covered by a protein corona that compromises the function of the nanoparticle core, changes the effective size of the nanoparticle, and determines its biological fate. Strategies developed to gain control over nanoparticles in biological fluids, particular in blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 82 publications
(150 reference statements)
0
14
0
Order By: Relevance
“…Therefore, the hydrated polymer brush contributes a repulsive osmotic potential and sterically blocks access to the core surface, as previously demonstrated. 20 , 43 , 44 However, the core displays a range of possible attractive vdW, charge, and hydrophobic interactions. Without a polymer brush, iron oxide nanoparticles rapidly aggregate and sediment in aqueous or protein dispersion (data not shown).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the hydrated polymer brush contributes a repulsive osmotic potential and sterically blocks access to the core surface, as previously demonstrated. 20 , 43 , 44 However, the core displays a range of possible attractive vdW, charge, and hydrophobic interactions. Without a polymer brush, iron oxide nanoparticles rapidly aggregate and sediment in aqueous or protein dispersion (data not shown).…”
Section: Results and Discussionmentioning
confidence: 99%
“… 5 , 31 Thus, the adsorption of serum proteins on nanoparticles is of the highest interest and relevance. 20 Nonspecifically adsorbed proteins in the corona can lead to reduced bioavailability and also trigger specific uptake and transport. Certain adsorbed and intact transport proteins, such as transferrin, have been reported to lead to increased intracellular uptake by cells, 31 , 32 while adsorption of opsonins is believed to increase clearance by the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…The compatibility of nonviral vectors with blood components is a key parameter for their suitability for direct administration into the circulatory system. [ 52 ] To exclude a damage of the erythrocyte membranes due to electrostatic interactions with the cationic polymers as an undesired side effect, the concentration dependent (0.024–50 µg mL −1 ) hemolytic activity of the free dextran esters was determined by spectrophotometric quantification of released hemoglobin from sheep erythrocytes after 1 h treatment representing typical circulation times in the blood. The hemolytic behavior was characterized in accordance with the ASTM F756‐08 standard.…”
Section: Resultsmentioning
confidence: 99%
“… 1 , 2 Formation of a protein corona is thought to lead to a loss in colloidal stability, and to clearance in vivo due to aggregation and recognition by the immune system. 3 6 A well-established strategy to hinder protein adsorption and provide steric stabilization to NPs relies on their functionalization with hydrophilic organic ligands. Theoretical and experimental studies of how the properties of nanoparticle shells influence the formation of the protein corona and interaction with serum proteins have concluded that preventing the formation of hydrophobic contacts by a hydrophilic shell is required to avoid the creation of a protein corona.…”
mentioning
confidence: 99%
“…A polymer shell that completely suppresses any corona formation in contact with serum proteins could be a game changer but has not been proposed yet. 6 If this objective were to be achieved, the interaction between biomolecules and engineered shells could be simultaneously controlled in a precise manner and enable many more applications in medicine and biotechnology. With this objective in mind, we turned our attention to cyclic polymers.…”
mentioning
confidence: 99%